RESPONSIBILITY ACCOUNTING AND MANAGERIAL PERFORMANCE EVALUATION: A QUALITATIVE STUDY OF A FOOD AND BEVERAGE ENTERPRISE - Fadilah Khoirunnisa; Reza Sukma Dara Yuniar; Jihan Salma Auliya' Desna (Universitas Tulungagung, 2024)
Responsibility accounting has become an essential management control tool for evaluating managerial performance by assigning accountability for controllable costs. However, its implementation in many small and medium-sized enterprises (SMEs), particularly in evaluating cost responsibility centers, remains limited. This study aims to examine the implementation of responsibility accounting as a managerial tool for evaluating the performance of the cost responsibility center at DMR Pull Tea Shop, a food and beverage enterprise. A qualitative research approach was employed using semi-structured interviews as the primary data collection method, supported by an analysis of the company's accountability reports. The collected data were analyzed descriptively to identify patterns related to budgeting practices, cost control, and managerial performance evaluation. The findings indicate that DMR Pull Tea Shop has implemented the fundamental principles of responsibility accounting through systematic accountability reporting and comprehensive documentation of operational expenditures. These practices enable management to monitor controllable costs, verify financial transactions, evaluate operational efficiency, and support informed managerial decision-making. Although the existing responsibility accounting system has not yet incorporated formal budget variance analysis or comprehensive performance indicators, it provides a practical foundation for strengthening managerial accountability and evaluating cost center performance. This study contributes to the management accounting literature by demonstrating how responsibility accounting can be effectively implemented in SMEs as a management control mechanism. Practically, the findings offer insights for SME managers seeking to improve financial accountability, operational efficiency, and performance evaluation through structured responsibility accounting practices.